Effect of multi-sized graphite filler on the mechanical properties and electrical conductivity - Nabilah Afiqah Mohd Radzuan,; Abu Bakar Sulong,; Iswandi, (Penerbit Universiti Kebangsaan Malaysia, 2021)
This research successfully fabricated conductive polymer composites (CPCs) prepared using multiple sizes of graphite filler (40, 100, 150, and 200 μm) that provided excellent network formation within the fillers and polypropylene matrix which further improved both electrical conductivity and flexural strength. An important discussion on the fabrication technique, including compression moulding and injection moulding was conducted, to manufacture CPC materials with a thickness less than 3 mm. The findings of this study suggested that fabricating CPCs using the compression moulding technique with a graphite composition of 75 wt. % exhibited better network connectivity as the electrical conductivity increased to 15 Scm-1. Also, compared to the three sizes of graphite filler (40/100/200 μm) it resulted in 13 Scm-1, with two sizes (40/200 μm) reporting better electrical conductivity at 15 Scm-1. This demonstrated that the addition of multiple sizes was not necessarily due to agglomeration occurring. The resultant graphite composites of 40/200 μm possessed a more stable structure having a thin composite layer (2.5 mm) which promoted better electrical conductivity suitable for bipolar plate used in proton exchange membrane fuel cells.